2004
DOI: 10.1002/app.20792
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel nitrogen‐containing flame retardant

Abstract: ABSTRACT:The lowering of ignitability and flammability of polyethylene (PE) and the production of fire-retarding materials has become an urgent problem because of the demand of fire safety. In our article, a new charring agent (CA), a derivative of triazines, was synthesized by charging 2-amino-4,6-dichloro-s-triazines and diethylenetriamine into a reactor to conduct the solution polycondensation reaction, and the synthetic conditions of monomer and CA, such as temperature, time, etc., were investigated. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 14 publications
0
68
0
1
Order By: Relevance
“…[ 6 ] Actually, graphene's unique 2D layered structure makes it seem to be having a retardant effect, for it can act as a carbon donor to allow an insulating cellular carbonaceous layer (char). [ 7 ] The 2D sheet structure, with lamellae blocking effect, can delay the heat transfer, pyrolysis products of diffusion and escape, and oxygen diffusion and mixing. [ 8 ] But these properties of graphene will hardly suffi ce.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Actually, graphene's unique 2D layered structure makes it seem to be having a retardant effect, for it can act as a carbon donor to allow an insulating cellular carbonaceous layer (char). [ 7 ] The 2D sheet structure, with lamellae blocking effect, can delay the heat transfer, pyrolysis products of diffusion and escape, and oxygen diffusion and mixing. [ 8 ] But these properties of graphene will hardly suffi ce.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, researchers have made great efforts to develop oligomeric or polymeric IFRs with relatively higher molecular weight and synergistic agent have been sued to enhance the flame retardancy of IFR [11][12][13][14]. The previous studies showed that some silicon-containing compounds, boron-containing compound, transitional metal oxides, 4A zeotile, metal compounds could serve as synergistic agents to increase the strength and stability of char layer to enhance the flame retardant performance of the composites [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, some halogen-containing compounds have been forbidden for use in many public places due to the release of toxic and corrosive gases which can choke people exposed to the fumes. The gases also corrode the metal equipment and pollute the environment [7][8][9][10][11]. Environment protectors have resisted the large-scale use of halogen-containing flame retardants and advocated the wide application of alternative chemical products [12].…”
Section: Introductionmentioning
confidence: 99%